2010
DOI: 10.1155/2010/692036
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Progression of Fibrosis on Liver Biopsy in Alaska Native and American Indian Persons with Chronic Hepatitis C

Abstract: The presence of type 2 diabetes mellitus, steatosis and duration of HCV infection were independent predictors of advanced fibrosis in the present cohort, with significant fibrosis progression demonstrated in persons who underwent serial biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Our finding that HCV infection acquired through blood transfusion is associated with higher rates of cirrhosis is in agreement with earlier retrospective studies that reported more aggressive histological inflammatory activity and a higher risk of hepatic decompensation in patients with transfusion-acquired hepatitis C (31,32). Our observation that duration of infection is a significant risk factor for the development of cirrhosis as assessed by FIB-4 corroborates earlier reports that showed duration of infection to be an independent predictor of advanced fibrosis in hepatitis C-infected individuals (33,34). Our observation that the duration of infection is positively associated with a higher likelihood of FIB-4-indicated cirrhosis also suggests that the FIB-4 test is a reliable predictor of cirrhosis.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that HCV infection acquired through blood transfusion is associated with higher rates of cirrhosis is in agreement with earlier retrospective studies that reported more aggressive histological inflammatory activity and a higher risk of hepatic decompensation in patients with transfusion-acquired hepatitis C (31,32). Our observation that duration of infection is a significant risk factor for the development of cirrhosis as assessed by FIB-4 corroborates earlier reports that showed duration of infection to be an independent predictor of advanced fibrosis in hepatitis C-infected individuals (33,34). Our observation that the duration of infection is positively associated with a higher likelihood of FIB-4-indicated cirrhosis also suggests that the FIB-4 test is a reliable predictor of cirrhosis.…”
Section: Discussionsupporting
confidence: 92%
“…Four studies evaluating progression from compensated to decompensated cirrhosis reported an incidence between 13-40% over a range of follow-up of 2.3-14.4 years. 15, 24, 31, 34 No clear pattern was identified between length of follow-up or patient characteristics and rate of outcomes. Notably, the definition of decompensation varied across studies.…”
Section: Resultsmentioning
confidence: 99%
“…19, 31 Variables found to be independently predictive of histologic progression are listed in Tables 2 and 4. Among all the variables assessed, baseline steatosis was most consistently reported as independently predictive of subsequent fibrosis progression (significant on multivariate analysis in 6 of 21 studies) with an odds ratio (OR) [(95% confidence interval (CI)] of 4.8 (1.3-18.3) to 14.3 (2.1-111.1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations